The control techniques drives and controls handbook - Drury, Bill (The Institution of Engineering and Technology, 2009)
Variable speed drives and the associated electrical motors play a central role in industry as well as the buildings in which one lives, work and are entertained. They are arguably the most potent tool in the quest to save energy and thereby reduce our carbon footprint. Their rate of development has been rapid and today's product is in many ways unrecognisable from its ancestors of even twenty years ago. Development continues for the components used in the products, the products themselves and the ways in which the products are used. This book contains a great deal of practical information for drives and industrial engineers who use motors and drives. It is a comprehensive guide to the technology underlying drives and motors. It contains sufficient theory to give both user and student an insight into the design of these components and thereby the constraints and opportunities that exist. It has been radically revised and expanded from the previous edition to contain much new information. The practical grounding of this book makes it a reference work that has a place on the shelf of students as well as practising engineers.